Talking about breast symmetry in the breast cancer clinic: What can we learn from an examination of clinical interaction? - Stephanie Mace; Sarah Collins; Susan Speer (Wiley, 2021)
Abstract Background Breast asymmetry is a common post‐operative outcome for women with breast cancer. Quality of cosmetic result is viewed clinically as a critical endpoint of surgery. However, research suggests that aesthetic standards governing breast reconstruction can be unrealistic and may problematically enforce feminine appearance norms. The aim of reconstructive procedures is to help women live well with and beyond breast cancer. Therefore, understanding how patients and clinicians talk about surgical outcomes is important. However, we lack evidence about such discussions. Objective To examine clinical communication about breast symmetry in real‐time consultations in a breast cancer clinic. Design Seventy‐three consultations between 16 clinicians and 47 patients were video‐recorded, transcribed and analysed using conversation analysis. Results In most cases, patients do considerable interactional work to persuade clinicians of the validity of their concerns regarding breast asymmetry, and clinicians legitimize these concerns, aligning with patients. In a significant minority of cases, patients appear more accepting of their treatment outcome, but clinicians prioritize symmetry or treat symmetry with the presence of breast tissue as normative, generating misalignment between clinician and patient. Conclusion Current clinical communication guidelines and practices may inadvertently reinforce culturally normative assumptions regarding the desirability of full, symmetrical breasts that are not held by all women. Clinicians and medical educators may benefit from detailed engagement with recordings of clinical communication like those analysed here, to reflect on which communicative practices may work best to attend to a patient's individual stance on breast symmetry, and optimize doctor‐patient alignment.